Ganoderma Lucidum: Extraction and Characterization of Polysaccharides, Yields and their Bioapplications - Y. Parepalli; M. Chavali; S. Reddy Pamanji; M. Singh (Algerian Journal of Research and Technology (AJRT), 2021)
The Reishi mushroom, Ganoderma lucidum is an edible herbal home remedy to boost the immune system, especially in the Asian countries. Its fruiting body can thrive well in a hot and humid climate and contain specific bioactive macromolecules like triterpenoids, phenolic compounds, steroids, nucleotides and their derivatives polysaccharides and glycoproteins which have strong therapeutic properties. In this mini-review, the focus is on medicinal G. lucidum polysaccharides, one of the effective constituents as a health-promoting agent and its methods of extraction and purification to reflect the current status of characterization techniques in clinical practices. An overview of conformational properties, different analytical techniques and other methods involved were briefly discussed. A detailed account of significant biological applications of G. lucidum polysaccharides like antitumor, anti-inflammatory, antiviral and anticancer activities was tabulated and discussed.